2002
DOI: 10.1016/s0092-8674(02)00813-9
|View full text |Cite
|
Sign up to set email alerts
|

Axonal Protein Synthesis Provides a Mechanism for Localized Regulation at an Intermediate Target

Abstract: As axons grow past intermediate targets, they change their responsiveness to guidance cues. Local upregulation of receptor expression is involved, but the mechanisms for this are not clear. Here protein synthesis is traced within individual axons by introducing RNAs encoding visualizable reporters. Individual severed axons and growth cones can translate proteins and also export them to the cell surface. As axons reach the spinal cord midline, EphA2 is among the receptors upregulated on at least some distal axo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
294
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(305 citation statements)
references
References 51 publications
9
294
0
2
Order By: Relevance
“…An RNA reporter construct consisting of green fluorescent protein (GFP) RNA followed by the 3Ј untranslated region (UTR) of EphA2 RNA was transfected into these neurons using electroporation. Brittis and colleagues (2002) found that GFP expression was specifically up-regulated in the distal axons and growth cones of these spinal neurons only after the axons crossed the midline, suggesting that a local protein synthesis mechanism was being activated in response to extracellular cues and was mediated by the EphA2 3ЈUTR sequence (Brittis et al 2002). These experiments provided evidence that localized protein synthesis is critical to rejuvenating and changing the growth cone's responsiveness to various environmental signals.…”
Section: Production Of the Building Blocks Both Membrane And Cytoplamentioning
confidence: 98%
See 1 more Smart Citation
“…An RNA reporter construct consisting of green fluorescent protein (GFP) RNA followed by the 3Ј untranslated region (UTR) of EphA2 RNA was transfected into these neurons using electroporation. Brittis and colleagues (2002) found that GFP expression was specifically up-regulated in the distal axons and growth cones of these spinal neurons only after the axons crossed the midline, suggesting that a local protein synthesis mechanism was being activated in response to extracellular cues and was mediated by the EphA2 3ЈUTR sequence (Brittis et al 2002). These experiments provided evidence that localized protein synthesis is critical to rejuvenating and changing the growth cone's responsiveness to various environmental signals.…”
Section: Production Of the Building Blocks Both Membrane And Cytoplamentioning
confidence: 98%
“…The specific induction of protein synthesis in axons was demonstrated beautifully using chick spinal cord axons, which normally up-regulate axonal expression of the EphA2 guidance receptor after crossing the midline (Brittis et al 2002). An RNA reporter construct consisting of green fluorescent protein (GFP) RNA followed by the 3Ј untranslated region (UTR) of EphA2 RNA was transfected into these neurons using electroporation.…”
Section: Production Of the Building Blocks Both Membrane And Cytoplamentioning
confidence: 99%
“…Only at the beginning of this century did work by Holt's group conclusively demonstrate that local protein synthesis is required for the chemotropic responses of axons to attractive and repulsive guidance cues [7]. This work heralded an extremely productive phase of research on local translation in developing axons, and now intra-axonal protein synthesis is recognized to be crucial for growth cone behavior [7][8][9][10][11][12][13][14], axonal pathfinding [15][16][17], axon maintenance [18], and retrograde signaling in developing axons [19,20]. However, far less is known about the extent and importance of localized protein synthesis in axons after the developmental period.…”
Section: Intra-axonal Protein Synthesismentioning
confidence: 99%
“…[95][96][97] Growth cones have 500-1000 ribosomes that provide a low basal level of protein synthesis, but which yield a marked increase in local protein synthesis in response to NTs. Additional neurite extension could occur by the cannibalization of lipids and proteins from the proximal axon via the ubiquitin-proteosome pathway -that is, a localized redistribution of axonal membrane to allow compensatory synapse growth after CNS injury.…”
Section: Clinical Descriptionmentioning
confidence: 99%